Lyapunov-based large-signal control of three-phase stand-alone inverters with inherent dual control loops and load disturbance adaptivity - He, Jinsong (2022)
In this article, existed Lyapunov-based control methods for stand-alone inverters either have a single control loop accompanied with steady-state errors or dual control loops at the sacrifice of negative definiteness of the derivative of the Lyapunov function. Besides, load-current sensors or observers are indispensable in these methods. Proposed Lyapunov-based control inherently has dual control loops that can rigorously guarantee the global large-signal stability of the system. Meanwhile, load disturbance is suppressed adaptively without any load-current sensors or observers. Stability analysis proves that the proposed method is valid both for a linear and nonlinear load. The proposed approach complies with the internal model principle, leading to the minimized steady-state error. An adaptive weighted Lyapunov function (V) is proposed to derive the dual-loop control law and adaptive law. The closed-loop system is inherently d-q decoupled. Three controller gains are tuned quantitatively via explicit formulas based on pole-placement strategy. Simulation and experimental results demonstrate that the proposed method has good steady-state and dynamic performance with great robustness against the parametric mismatch.